Readings in Romans: interpreting Paul's apocalyptic gospel - Gaventa, Beverly Roberts (Baylor University Press, 2025)
"Anthologizes over two decades of Gaventa's essays and articles on the message and theology of Paul's Letter to the Romans"-- Provided by publisher